Criminal Liability for Corporations in Handling Environmental Damage in the Cisalada River: Case Study at PT QL Agrofood - Ramdani, Wildan; Dwidja Priyatno; Rusman; Kristian (Yayasan Studi Cendekia Indonesia (YSCI), 2024)
Environmental destruction by corporations often presents significant legal challenges, especially in establishing criminal liability. This article examines the aspects of criminal liability that can be applied to PT QL Agrofood in the case of environmental pollution and destruction in the Cisalada River. Based on this case study, an in-depth analysis of relevant environmental regulations and law enforcement mechanisms is conducted, particularly in relation to Law Number 32 of 2009 concerning Environmental Protection and Management and other relevant regulations. The main focus of this research is to assess whether Indonesia's legal structure is effective enough in reaching and taking action against corporations responsible for environmental destruction. The results show the impact on corporations and communities close to PT Ql Agrofood, as well as efforts in environmental protection and management. Using normative and empirical approaches, this article recommends improvements to regulations that can strengthen the principle of criminal liability for corporations in cases of environmental pollution.